British architecture in Peninsular Malaysia: an analytical study of architectural characteristics for colonial buildings in hill stations / Abu Bakar Hj. Abd. Raub - Abd. Raub, Abu Bakar (Institute of Graduate Studies, UiTM, 2018)
The roots of the colonial buildings in Peninsular Malaysia hill stations lie in the early attempts of British colonization to build a cool retreat or the 'Little England' for British military and comrade traders. There are many colonial buildings that rich in history and architectural merits but are in a state of deterioration and dilapidation in hill stations of Peninsular Malaysia. Due to that, there is a dire need to protect and to restore these buildings heritage but one needs to have accurate technical knowledge and systematic documentation. The purpose of this research is to provide an accurate roster as a valuable reference and also to determine the methods and techniques of building masonry construction and materials of colonial buildings that reflected the characteristics of British Architecture. The research has been carried out in two main methods, which are the primary and secondary data collections. The primary data is obtained from selected case studies and the fieldwork includes building inventory, photo recording, visual analysis, measured drawing and semi-structured interviews. Meanwhile, the secondary data are gathered from literature review, which include books on history, building construction, restoration and conservation, and data on British colonial architecture. Secondary data also include articles, journals, newspapers, websites, and magazines with particular reference to colonial architecture in United Kingdom, India and Malaysia…